Monitoring air quality in residential areas with low-cost sensors: Santa Cecilia case - Oscar Arnulfo Fajardo-Montaña; Yeimy Alejandra Salinas; Carlos Reyes; Daniel Santiago Becerra-Casas (Revista Facultad de Ingeniería Universidad de Antioquia)
The expansion of the industrial zone along the Medellín Highway on the northwestern outskirts of Bogotá has raised concerns among nearby residents regarding the potential health impacts of pollutant emissions. This study evaluates the behaviour of particulate matter with an aerodynamic diameter below 2.5 micrometres (PM2.5) in indoor environments of the Santa Cecilia neighbourhood, relative to outdoor atmospheric concentrations, using custom-designed low-cost sensors. In situ PM2.5 concentrations were compared with meteorological data and PM2.5 reports from the Bogotá Air Quality Monitoring Network (RMCAB). Data processing and wind analysis were conducted using Python and WRPLOT software. The results indicate that indoor PM2.5 concentrations are minimally influenced by outdoor pollutants (approximately 3%), with peaks of internal concentrations (up to 1661 µg/m³) attributed primarily to indoor activities and personal behaviours. Recommendations include the strategic use of natural ventilation to prevent excessive indoor PM2.5 accumulation during activities such as cooking and cleaning.